1994
DOI: 10.1021/ma00102a039
|View full text |Cite
|
Sign up to set email alerts
|

Narrow Polydispersity Polystyrene by a Free-Radical Polymerization Process-Rate Enhancement

Abstract: We recently reported the synthesis of resins, by a freeradical polymerization process, with polydispersities (PDs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
142
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(145 citation statements)
references
References 1 publication
3
142
0
Order By: Relevance
“…Georges et al 147 demonstrated that the addition of CSA to a benzoyl peroxide (BPO)-initiated, TEMPOmediated polymerization of styrene increased the molecular weight and monomer conversion and decreased the polydispersity. Because free-radical styrene polymerization in the absence of nitroxide is not affected by the addition of CSA, it was deduced that CSA interacts with the nitroxide.…”
Section: Scheme 4 Schemementioning
confidence: 99%
“…Georges et al 147 demonstrated that the addition of CSA to a benzoyl peroxide (BPO)-initiated, TEMPOmediated polymerization of styrene increased the molecular weight and monomer conversion and decreased the polydispersity. Because free-radical styrene polymerization in the absence of nitroxide is not affected by the addition of CSA, it was deduced that CSA interacts with the nitroxide.…”
Section: Scheme 4 Schemementioning
confidence: 99%
“…These results are quite unusual if compared to those obtained for polystyrene synthesized via SFRP under nearly identical conditions. High molecular weight polystyrene (M -n A 10 000 Dalton) can be obtained at similar rates in high yield by SFRP only if particular additives, which help to increase the rate of polymerization, are present in the reaction mixture [20][21][22][23] . It was observed that this approach was unnecessary for formation of PBBOS.…”
Section: Synthesismentioning
confidence: 99%
“…This implies that scission occurs more easily when the linkage is between CPT and the growing radical than when it is with MPT and OPT. This may be accounted for by the fact that triphosphazene pentachloride of CPT acts as a Lewis acid for the growing chain end to advance polymerization, when it is taken into consideration that an acid 11 and organic acid salt 12 forwards TEMPO-mediated polymerization. Polymer- ization by OPT is faster than that by MPT.…”
Section: Resultsmentioning
confidence: 99%